Mostly straight : sexual fluidity among men - Savin-Williams, Ritch C. (Harvard University Press, 2017)
In this manuscript, Savin-Williams explores the phenomenon of young men who identify themselves as "mostly straight." What does the small, but growing, number of young men who identify as mostly straight mean for our understanding of sexual orientation, sexual identity, and sexual behavior? What does it say about our understanding of masculinity, our understanding of sex and gender differences (e.g., women are more likely to identify as "mostly straight"), and the future of sexual identity politics? This manuscript is a culmination of Savin-Williams's research on male sexual fluidity. It explores a host of topics: whether we should conceive of sexual orientation as a category or a spectrum or as something else entirely; why some men who engage in sexual behavior with both men and women identify as "bisexual" and others as "mostly straight," and still others who do so simply identify as either "straight" or "gay"; the stability of "mostly straight" as a sexual identity (i.e., to what degree is "mostly straight" a temporary identity or a way-station on an individual's journey from straight to gay or bisexual); what biological/psychological factors might correlate with being "mostly straight"; how have changes in popular/vernacular understanding of sexuality and sexual behavior affected the development of sexuality identity in boys and men. The manuscript draws on a wide body of research, but focuses on in-depth interviews with 40 different individuals from the "millennial" generation. It focuses on key developmental milestones, including first sexual memories, first crushes, coming out to friends and families, and first adult relationships. It examines how the lives of "mostly straight" men compare to those of men who identify as straight, gay, or bisexual.--